2014
DOI: 10.1371/journal.pone.0091052
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Spontaneous Oscillatory Activity to Tonic Heat Pain

Abstract: Transient painful stimuli could induce suppression of alpha oscillatory activities and enhancement of gamma oscillatory activities that also could be greatly modulated by attention. Here, we attempted to characterize changes in cortical activities during tonic heat pain perception and investigated the influence of directed/distracted attention on these responses. We collected 5-minute long continuous Electroencephalography (EEG) data from 38 healthy volunteers during four conditions presented in a counterbalan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

23
126
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(157 citation statements)
references
References 65 publications
(138 reference statements)
23
126
2
6
Order By: Relevance
“…The attention modulation of pain related alpha activity was also observed in tonic 7 pain studies (Peng et al, 2014). With the delivery of 5-min tonic heat painful stimuli, 8 the effect of selective attention was characterized as a significant and consistent 9 decrease of spontaneous alpha oscillatory activity over somatosensory areas 10 contralateral to the stimulated side, by comparing the alpha activity in 11 nociceptive-attended (rating the stimulus intensity at the end of each minute) and (Liu et al, 2011a;Liu et al, 8 2011b).…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…The attention modulation of pain related alpha activity was also observed in tonic 7 pain studies (Peng et al, 2014). With the delivery of 5-min tonic heat painful stimuli, 8 the effect of selective attention was characterized as a significant and consistent 9 decrease of spontaneous alpha oscillatory activity over somatosensory areas 10 contralateral to the stimulated side, by comparing the alpha activity in 11 nociceptive-attended (rating the stimulus intensity at the end of each minute) and (Liu et al, 2011a;Liu et al, 8 2011b).…”
mentioning
confidence: 64%
“…It is quite likely that attention 19 exerts its effect on pain perception through modulating the coherence of ongoing 20 oscillations selectively for the neurons involved in encoding attended stimuli. 21 22 Therefore, the attention modulation of pain (i.e., clear influences on the sensory and 23 affective dimensions of pain experience) could be mediated by changes of alpha 24 oscillatory activities (Foxe and Snyder, 2011;Hauck et al, 2007;Hu et al, 2013;May 25 et al, 2012;Ohara et al, 2004;Peng et al, 2014). The intensified alpha suppression 26 within pain-related brain areas (e.g., somatosensory cortex) due to attention directed 27 to pain, is quite likely reflecting attentional augmentation of painful information 28…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,5,48 Although our data show a link between the ACCinduced output and the centroparietal gBO (given the clinical-electrophysiological correlations), the fact that this correspondence could be a marker of ongoing consciousness generation and maintenance, requiring multiple and integrated brain activations, 22,23 is debatable. Although it has been shown that gBO in the centroparietal region could be related to pain processing, regardless of the stimulus repetition or the attention level, 36,42,66,91 and that it may have a key role in the sensorimotor transformation of pain (given the correlation with reaction time speediness in animal and human experimental models), 40,90 the pain-induced gBO may also be related to automatic attention-related pain processing. 82 Nonetheless, a correlation between activation of the ACC and the pain-control parietal networks has been shown previously.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy individuals, cortical pain processing mechanisms (depending on wide frontoparietal networks) 12 can be studied through analysis of nociceptive-induced g-band oscillatory activity (gBO) within centroparietal areas, without any substantial need for the individual's participation or cognitive/ motor output. 36,66 Nociceptive-induced gBO may represent a marker of conscious and subjective pain perception, the access of the neural process regarding nociceptive and salient stimuli to a higher conscious level, or the summary effects of bottom-up and topdown processes concerning pain modulation. 77,81 Within the wide frontoparietal network, the anterior cingulate cortex (ACC) could have a striking role in pain processing and gating at the cortical level.…”
mentioning
confidence: 99%